Comparative immunogenicity of urea and EDTA extracted cell surface components from Salmonella typhimurium in mice - Chaturvedi, G C; Minakshi, Minakshi; Kaura, Y K; Pruthi, A K (The Indian Journal of Animal Sciences, 2012)
Swiss albino mice (group 1a to 4g) immunized with urea extracted cell surface components (UECSCs), recycled UECSCs, peak I(PI), recycled UECSCs pooled peaks (PI+PII+PIII) and EDTA extracted CSCs of S. typhimurium 163, respectively, showed humoral(HIR) and cellular immune responses (CIR). The HIR was exhibited by increase in immunoglobulin (Ig) level at weekly intervalspostimmunization (PI) and postchallenge (PC), and immediate type footpad thickness (ITFT) at 6 hr postinoculation ofeliciting antigen (PEA) in the left hind footpad. However, the mice in group 4f immunized with EDTA extracted esc showedcomparatively higher level of Ig at 4 weeks PI and 3 weeks PC. In immunized mice treated with carrageenan (group 1b, 2d, 4g),the 19 level decreased abruptly at 1.2 and 3 weeks PC. The CIR was exhibited by delayed type footpad thickness (DTFT) at 72hr PEA, nitroblue tetrazolium (NBT) reduction test at weekly intervals PI and PC, Postchallenge heavy mortality was observedin mice treated with carrageenan (macrophage depleted).The difference between the percent protection of immunized groups (1 a, 2c, 3e) as well as immunized and carrageenan Â treatedgroups (1b, 2d) and mock vaccinated group (5h) was statistically significant. The corresponding values in groups i.e. 4f, 4gand 5h, were highly significant. The liver and spleen of the sacrificed mice surviving challange in the immunized groupsshowed more immunological, less immunopathological and Pathological alterations on microscopic examination. while mice ingroup 4f showed only immunological alterations. The EDTA extracted CSCs were more immunogenic and protective compared toUECSCs in mice.